2022
DOI: 10.3390/molecules27196233
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Sulfonamides and Tetracyclines in Meat during Pan Cooking: Focus on the Thermodegradation of Sulfamethoxazole

Abstract: Although antimicrobials are generally found in trace amounts in meat, the human health risk they bear cannot be ignored. With the ultimate aim of making a better assessment of consumer exposure, this study explored the effects of pan cooking on sulfonamides and tetracyclines in meat. Screening of these antimicrobials in cooked meat was first performed by the European Union Reference Laboratory on the basis of HPLC-MS/MS analyses. A proof of concept approach using radiolabeling was then carried out on the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
1
0
2
Order By: Relevance
“…Sulfonamide is a broad-spectrum antibiotic, primarily bacteriostatic, and mainly used in gastrointestinal infections, leptospirosis, mycoplasmosis, and pasteurellosis. Planche et al [32] studied "the fate of Sulfonamide in meat during pan cooking and observed that cooking induced significant antimicrobial losses of up to 45% for sulfamethoxazole. However, six potential degradation products of 14 C-sulfamethoxazole were detected in the cooked meat.…”
Section: Stability Of Sulfonamidementioning
confidence: 99%
“…Sulfonamide is a broad-spectrum antibiotic, primarily bacteriostatic, and mainly used in gastrointestinal infections, leptospirosis, mycoplasmosis, and pasteurellosis. Planche et al [32] studied "the fate of Sulfonamide in meat during pan cooking and observed that cooking induced significant antimicrobial losses of up to 45% for sulfamethoxazole. However, six potential degradation products of 14 C-sulfamethoxazole were detected in the cooked meat.…”
Section: Stability Of Sulfonamidementioning
confidence: 99%
“…Le projet a impliqué 5 laboratoires nationaux de références (LNR) appartenant à l'ANSES pour quatre d'entre eux et à l'ONIRIS pour le cinquième. Ces LNR ont pris en charge les analyses des différentes familles de micropolluants [3,4,6,7,24] dans l'ensemble des échantillons. Les mesures de contamination ont été croisées avec des évaluations de fréquence de consommation des viandes [25] et corrigées des effets modulateurs potentiellement induits par la cuisson [5,6] et la digestion [26] afin d'évaluer l'exposition à ces micropolluants.…”
Section: Le Projet Someatunclassified
“…Les aliments sont en effet susceptibles de contenir un large éventail de ces « contaminants » chimiques transférés ou générés le plus souvent à l'état de traces à différentes étapes de leur chaîne d'élaboration [2]. En amont de la chaîne, au stade de la production des matières premières, il s'agit de polluants de l'environnement comme les polluants organiques persistants (POPs), tels que les dioxines [3], ou les éléments trace métalliques (ETMs), tels que le plomb [3,4], de résidus de traitements de la production agricole, qu'ils soient phytosanitaires, tels que des pesticides organophosphorés [5], ou vétérinaires tels que les antibiotiques sulfamides [6], et de substances chimiques d'origine microbienne produites au cours du stockage comme les mycotoxines [7]. Au stade de la transformation des matières premières en produits transformés, il peut s'agir d'ingrédients ajoutés au cours des étapes de formulation comme certains additifs alimentaires, de substances toxiques néoformées au cours de procédés de transformation tels que les hydrocarbures aromatiques polycycliques [8] ou issus de matériaux de contact des aliments comme les migrants d'emballage tels que le bisphénol A [9].…”
Section: Introductionunclassified